Diagnóstico, manejo e prognóstico do tratamento da crise tirotóxica em centro terciário - Vieira, Isabel Christina De Oliveira [UNIFESP] (2020)
Background: Thyroid storm (TS) is a life-threatening medical emergency characterized by an exacerbation of thyrotoxicosis associated with decompensation of one or more organs or systems. However, it is rare and scarcely studied, with only a few recent studies in the literature and in Brazil. Materials and methods: We evaluated TS patients treated between 2013 and 2017. TS was characterized by multisystemic thyrotoxicosis (fever, cardiovascular, gastrointestinal/hepatic, neurological disorder) and compatible laboratory profile (suppressed thyroid stimulating hormone and elevated free T4). Epidemiological, clinical, complementary exam, treatment, and evolution data were collected. Results: The mean age of patients was 41.4 years, and 43/56 patients were women. Graves’ disease was the main cause of thyrotoxicosis; half of the patients did not know the diagnosis of hyperthyroidism before hospitalization, with a mean time between diagnosis and hospitalization of 24 months. Over half of the cases had a family history of autoimmunity. A triggering factor was observed in 48 episodes, with nonadherence (50%) and infection (45.8%) being the most frequent. There was no statistical difference in the presentation of clinical symptoms when compared by gender. The average length of stay was 14.2 ± 26.7 days, being longer in male patients. Mortality occurred in a significant number of cases (10.7%). Conclusion: Surprisingly, ignorance of the diagnosis of thyrotoxicosis was a widespread event in the cases of TS in our country. As expected, poor adherence and infection were the most common precipitating factors. In modern times, TS remains a significant cause of morbidity and mortality associated with decompensated.